Cytokine storm in COVID-19: pathogenesis and overview of anti-inflammatory agents used in treatment - ATAGÜNDÜZ, IŞIK (SPRINGER LONDON LTD, 2020)
COVID-19 infection has a heterogenous disease course

it may be asymptomatic or causes only mild symptoms in the majority of the cases, while immunologic complications such as macrophage activation syndrome also known as secondary hemophagocytic lymphohistiocytosis, resulting in cytokine storm syndrome and acute respiratory distress syndrome, may also occur in some patients. According to current literature, impairment of SARS-CoV-2 clearance due to genetic and viral features, lower levels of interferons, increased neutrophil extracellular traps, and increased pyroptosis and probable other unknown mechanisms create a background for severe disease course complicated by macrophage activation syndrome and cytokine storm. Various genetic mutations may also constitute a risk factor for severe disease course and occurrence of cytokine storm in COVID-19. Once, immunologic complications like cytokine storm occur, anti-viral treatment alone is not enough and should be combined with appropriate anti-inflammatory treatment. Anti-rheumatic drugs, which are tried for managing immunologic complications of COVID-19 infection, will also be discussed including chloroquine, hydroxychloroquine, JAK inhibitors, IL-6 inhibitors, IL-1 inhibitors, anti-TNF-alpha agents, corticosteroids, intravenous immunoglobulin (IVIG), and colchicine. Early recognition and appropriate treatment of immunologic complications will decrease the morbidity and mortality in COVID-19 infection, which requires the collaboration of infectious disease, lung, and intensive care unit specialists with other experts such as immunologists, rheumatologists, and hematologists.
Keywords: COVID-19; Cytokine storm syndrome; Hemophagocytic lymphohistiocytosis; Macrophage activation syndrome; RESPIRATORY SYNDROME CORONAVIRUS; HOST-DEFENSE; CHLOROQUINE; INFECTION; VIRUS; EFFICACY; MDA5